2023
DOI: 10.1021/acsami.2c21187
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Functionalized Metal–Organic Frameworks for Binding Coronavirus Proteins

Abstract: Since the outbreak of SARS-CoV-2, a multitude of strategies have been explored for the means of protection and shielding against virus particles: filtration equipment (PPE) has been widely used in daily life. In this work, we explore another approach in the form of deactivating coronavirus particles through selective binding onto the surface of metal–organic frameworks (MOFs) to further the fight against the transmission of respiratory viruses. MOFs are attractive materials in this regard, as their rich pore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The efficacy of MOF systems may be enhanced by functionalizing with other antiviral agents such as folic acid or carotenoids. One example is a proof-of-concept study by Desai et al, which showed that MOFs can be surface-functionalized with folic acid (FA), nystatin (Nys), or tenofovir (Teno) and bind to viral capsid proteins . This would immobilize the viruses and prevent them from replicating.…”
Section: Antiviral Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of MOF systems may be enhanced by functionalizing with other antiviral agents such as folic acid or carotenoids. One example is a proof-of-concept study by Desai et al, which showed that MOFs can be surface-functionalized with folic acid (FA), nystatin (Nys), or tenofovir (Teno) and bind to viral capsid proteins . This would immobilize the viruses and prevent them from replicating.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Recently, MOFs have been employed to produce filters, masks, and other materials with biocidal activity for public health protection. MOFs are great candidates for textile materials because of their vast design possibilities; their easily manipulated structure and porosity also present the opportunity for high filtration efficiency and pathogenic protection. , …”
Section: Personal Protective Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs) are extended coordination solids that typically form as crystalline or microcrystalline particles with a variety of rich pore structures . The modification of the external surfaces of MOF via coordination chemistry is critical to many features of these materials, particularly the modulation of their nucleation/growth as well as the immobilization of small molecules or polymers for a variety of applications. Despite many studies that rely on the surface chemistry of MOFs, few studies have quantified these interactions. , This is probably due, in part, to the porous nature of the MOF surface, which creates some ambiguity about where (interior vs exterior) and how molecules interact with the framework.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of metal–organic frameworks (MOFs) have expanded into various fields including biomedical, 1–3 energy storage, 4–6 environmental, 7–10 sensors, 11–14 magnetism, 15–17 catalysis, 18–20 gas capture and storage, 21–26 etc. These applications depend in part on the discovery of new structures and methods.…”
Section: Introductionmentioning
confidence: 99%